Proton pump inhibitors may enhance the risk of citalopram‐ and escitalopram‐associated sudden cardiac death among patients receiving hemodialysis. Issue 6 (24th March 2022) - Assimon, Magdalene M.; Pun, Patrick H.; Al‐Khatib, Sana M.; Brookhart, M. Alan; Gaynes, Bradley N.; Winkelmayer, Wolfgang C.; Flythe, Jennifer E.
Abstract: Purpose: Polypharmacy is common in the hemodialysis population and increases the likelihood that patients will be exposed to clinically significant drug–drug interactions. Concurrent use of proton pump inhibitors (PPIs) with citalopram or escitalopram may potentiate the QT‐prolonging effects of these selective serotonin reuptake inhibitors through pharmacodynamic and/or pharmacokinetic interactions. Methods: We conducted a retrospective cohort study using data from the U.S. Renal Data System (2007–2017) and a new‐user design to examine the differential risk of sudden cardiac death (SCD) associated with citalopram/escitalopram initiation vs. sertraline initiation in the presence and absence of PPI use among adults receiving hemodialysis. We studied 72 559 patients:14 983 (21%) citalopram/escitalopram initiators using a PPI; 26 503 (36%) citalopram/escitalopram initiators not using a PPI;10 779 (15%) sertraline initiators using a PPI; and 20 294 (28%) sertraline initiators not using a PPI (referent). The outcome of interest was 1‐year SCD. We used inverse probability of treatment weighted survival models to estimate weighted hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Compared with sertraline initiators not using a PPI, citalopram/escitalopram initiators using a PPI had the numerically highest risk of SCD (HR [95% CI] = 1.31 [1.11–1.54]), followed by citalopram/escitalopram initiators not using a PPI (HR [95% CI] = 1.22 [1.06–1.41]). Sertraline initiators using a PPI had a similar risk of SCD compared with those not using a PPI (HR [95% CI] = 1.03 [0.85–1.26]). Conclusions: Existing PPI use may elevate the risk of SCD associated with citalopram or escitalopram initiation among hemodialysis patients.